Letter (copy) : Assistance to Republican Spaniards - Tewson, Vincent
1949-09-30 038-0002-002 2. suggestion of our undertaking the welfare work cannot be accepted, we have no desire to interfere with the interest which has been shown by certain organisations in the work in which she has been engaged. I have suggested that she should make contact with the Spanish Group to which I have referred above and talk the matter over with them to see how far they can assist. The answer to your letter, therefore, is that, whilst the General Council will not be initiating any action with affiliated Unions, they would not desire to discourage anyone who wished, because of their long association with the work, to maintain contact and support. Yours sincerely, General Secretary. 292/946/38/2(II)